Antifungal Activity of Brevundimonas diminuta AgainstFusarium oxysporum on Tomato Plants under Greenhouse Condition - Al attar, Nagham; ALdeen, Sana; Al Shahwany, Ayyad (Iraqi Journal of Science, 2025)
Eighty one bacterial isolates were obtained from 53 soil samples of different plants rhizosphere. All the isolated bacterial were screened for antifungal effect against Fusarium oxysporum. Three isolates gave antifungal activity with inhibition zone ranged between (0.5-2.5 cm). Two isolates (Bd1 and Bd2) were Brevundimonas diminuta, while the third(Pf1) was Pseudomonas fluorescence .B.diminuta(Bd1) which used in this study isolated from Raphanus sativus gave the highest inhibitionzone against F. oxysporum.In green house experiment , seedling of tomato cultivar Lycopersicon esculentum . var. commune were treated with two concentration 1012 cell/ml(B12 ) ,1014 cell/ml (B14) of B.diminuta (Bd1) and planted in soil mixed with106 spores/gm(F) of F. oxysporum one day before seedling planting. . The growth parameters(percentage in leaf area , total chlorophyll , percentage for fresh and dry weight) were recorded after 60 days.Also ,FLC analysis were used todetectthe hormones in plant leaves. The result showedsignificant increased in growth characters by (FB14) treatmentcompared with (CF) treatment(tomato plant infected byF. oxysporum only). The plant growth parameters values correspondingly increased by increasing bacterial dose. While the FLC analysis for the hormones showed increasing percentage for the Indole acetic acid , gibberellic acid and cytokinine group (Kintein ,Zatain and Benzyl adenine) under FB14 treatment compared with CF treatment , respectively . Beside ,The Abscisic acid hormone which promote for plant resisting against fungi was significant increasedwith FB14 treatment .The B. diminuta (Bd1) is reported for the first time prove effective useful for their establishment and proliferation in soil for antifungal effect against F.oxysporum.Also, this is first time using B. diminuta (Bd1) cultural as well as plant growth promoting rhizobacteria (PGPR) functional for tomato crop.